Unlocking the potential of M records: examining its economic contributions and future prospects in the entertainment sector of Bangladesh - Ieasmin, Farzana (Brac University, 2024)
This case study is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2023.